European Youth Labour Markets Problems and Policies (Springer International Publishing, 2018)
This timely analysis examines the complex state of youth unemployment across Europe and offers cogent policy suggestions for addressing this longstanding societal problem. The findings reveal numerous national and regional factors affecting youth joblessness-not only market and economic challenges, but also deep sociocultural and political dynamics underlying the situations. Coverage details how the standard transition from school to work is disrupted in an already depressed adult job market, and compares a wide range of responses in terms of both young people's educational decision-making and national youth policy. In particular, contributors assess whether the current crop of Youth Guarantee programs can/should be a model for employment policy across the continent. Among the topics covered: Youth labour market prospects and recent policy developments. Youth labour market in Central and Eastern Europe. Early school dropout in Spain: evolution during the Great Recession. Overeducation among European university graduates: a constraint or a choice? Promoting youth employment in Europe: evidence-based policy lessons. The evaluation of a Finnish youth guarantee: lessons for Europe? European Youth Labour Markets is of interest to an international audience of economists, sociologists, and leaders in governmental, non-profit, and corporate sectors through its broad and comparative macroeconomic focus and implications for policymaking, research, resource allocation, and policy evaluation. .